Pengembangan Bahan Ajar Bahasa Arab - Abusyairi, Khairy (Dinamika Ilmu, 2013)
Up to day, the materials of Arabic teaching that are developed and used widely in Indonesia in general are the teaching materials used in the madrassah in the Middle East. If the teaching material is the result of the development of amounts not so much. While the demands for innovation and the development of Arabic language teaching materials, today continues to roll, in line with the dynamics of the development of science and technology. Besides that , the demand for Arabic teaching materials that use Indonesian as the language develops in most introductory students, especially those with a general educational background. Thus, one needs to have a competence of teachers in performing their duties is developing instructional materials. Development of teaching materials a teacher is important for learning more effective, efficient, and does not deviate from the competency achieved. Arabic teaching materials can be developed through the following steps : a) analysis, b ) design, c ) the writing and preparation of the material, d ) evaluation, e ) revision.